Women's health: Beyond reproductive years - Vibha; Ananya Ray Laskar (Wolters Kluwer Medknow Publications, 2011)
With changing demographic profile India has more older women than men as life expectancy for women is 67.57 as against 65.46 for men. Gender differences in the aging process reflect biological, economic, and social differences. Both social and health needs of the older women are unique and distinctive as they are vulnerable. The social problems revolve around widowhood, dependency, illiteracy and lack of awareness about the policies and programmes from which they can benefit. Among the medical problems, vision (cataract) and degenerative joint disease top the list, followed by neurological problems. Lifestyle diseases form another single-most important group of health problems in the elderly women. The risk of cardiovascular disease doubles with the outcome being poorer than men. The most common causes of death among women above the age of 60 years are stroke, ischemic heart disease and COPD. Hypertensive heart disease and lower respiratory tract infections contribute to mortality in these women. Common malignancies viz. Cervical, breast and uterus in women are specific to them and account for a sizeable morbidity and mortality. In a study done at Lady Hardinge medical college in Delhi, Hypertension (39.6%) and obesity (12-46.8%) were very common in postmenopausal women. Half or more women had high salt and fat intake, low fruit and vegetable intake and stress. There is a need to recognize the special health needs of the women beyond the reproductive age, to be met through strengthening and reorienting the public health services at all levels starting from primary health care to secondary till tertiary care level with adequate referral linkages. All policies and programs need to have a gender perspective. At present there is lack of sensitization and appropriate training of the health personnel in dealing with the needs of elderly. Women too need to be aware to adopt healthy lifestyle and seek timely care.